As contribuições da climatologia para prevenção e combate a incêndios florestais no Parque Estadual Serra do Rola Moça - Leonardo Debossan de Oliveira (2023)
Wildland fires occur in all Brazilian biomes, causing significant environmental damage in each region. These fires negatively affect the hydrological cycle, the carbon cycle in the atmosphere, biodiversity and natural resources. In the case of the Brazilian Cerrado, fires occur more frequent between July and October, due to the severe reduction in rainfall and the low relative humidity of the air, combined with the physiology of the plants in the biome. Although fire is necessary for some species in the Cerrado, the high frequency and intensity of fires can cause environmental damage to fauna, flora and the anthropized environment. The Serra do Rola Moça State Park (PESRM), located in Minas Gerais, is an important Conservation Unit that supplies water to most people in the metropolitan region of Belo Horizonte. In addition, the park is home to plant and animal species, some of which are endemic. However, the park annually faces problems caused by wildland fires. Despite efforts to contain fires, it is necessary to incorporate new prevention and combat techniques. Integrated Fire Management (MIF) is a strategy used in other countries and recently implemented as fire prevention in federal Conservation Units. However, the state of Minas Gerais faces challenges due to the lack of research on climatic parameters for performing this type of prescribed burning. The general objective of this study is to develop a methodological proposal for Integrated Fire Management in Serra do Rola Moça State Park. The specific objectives include calculating the water balance of the park region, climatological analysis, the relationship between burned areas and atmospheric conditions, and analysis of the results in order to understand the behavior of fire in the Conservation Unit. The research seeks to answer the following questions: how can climatology analysis categories help in the safe and integrated execution of the FIM? Which months have the best weather conditions for the implementation of the MIF? What are the atmospheric states in which major wildfire events occur? The research resulted in a methodological proposal for the Integrated Fire Management in the Serra do Rola Moça State Park, considering the factors that influence wildland fires and climatic seasonality. The results demonstrated the effectiveness of calculating the water balance to diagnose the critical period for the occurrence of fires in the conservation area, with the aim of protecting biodiversity, ecosystems and local communities. The delimitation of inappropriate periods for prescribed burning seeks to balance the natural dynamics of fire and human needs and perform the procedure in a safer way. It is expected that this proposal will be applied in other regions, contributing to the preservation of natural resources.